THE RELATIONSHIP OF LANGUAGE ATTITUDE AND CREATIVITY ON ENGLISH SPEAKING PROFICIENCY - Irma Nuraini; Nurjanah Nurjanah; Engliana Engliana (INFERENCE: Journal of English Language Teaching, 2018)
The purpose of the research is to figure out three aspects: 1) the influence of language attitude and creativity together with the skills of English speaking students; 2) Influence of language attitude towards English speaking skills; 3) Influence of creativity in the students’ speaking skills. The method used in this research is method is survey research. The population in this research is the students of the class/levels of XI SMK Negeri in Purwakarta district of West Java province, consisting of two different schools, with overall 944 students.  The results of the study concluded that: first, there is a significant influence of language attitude and creativity together with the skills of speaking English students by the acquisition of the value of Sig. 0.000 < 0.05 and Fh = 14.697. Second, there is a significant influence of speaking attitude towards English speaking skills; this is evidenced by the acquisition of the value of GIS. 0.000 < 0.05 and th = 3.765. 3). At last, there is a significant influence on the power of creativity in English speaking skills by the acquisition of the value of Sig. 0.007 < 0.05 and th = 2.746.Keywords: language attitude; speaking skills; foreign language learning; creativity.